Facile synthesis of nanostructured Ni/NiO/N-doped graphene electrocatalysts for enhanced oxygen evolution reaction - Madampadi, Roshni; Patel, Avit Bhogilal; Vinod, C. P.; Gupta, Ritu; Jagadeesan, Dinesh (Nanoscale Advances, 2024)
Electrocatalysts containing a Ni/NiO/N-doped graphene interface have been synthesised using the ligand-assisted chemical vapor deposition technique. NiO nanoparticles were used as the substrate to grow N-doped graphene by decomposing vapours of benzene and N-containing ligands. The method was demonstrated with two nitrogen-containing ligands, namely dipyrazino[2,3-f:2 `,3 `-h]quinoxaline-2,3,6,7,10,11-hexacarbonitrile (L) and melamine (M). The structure and composition of the as-synthesized composites were characterized by XRD, Raman spectroscopy, SEM, TEM and XPS. The composite prepared using the ligand L had NiO sandwiched between Ni and N-doped graphene and showed an overpotential of 292 mV at 10 mA cm-2 and a Tafel slope of 45.41 mV dec-1 for the OER, which is comparable to the existing noble metal catalysts. The composite prepared using the ligand M had Ni encapsulated by N-doped graphene without NiO. It showed an overpotential of 390 mV at 10 mA cm-2 and a Tafel slope of 78.9 mV dec-1. The ligand-assisted CVD route demonstrates a facile route to control the microstructure of the electrocatalysts. Electrocatalysts containing a Ni/NiO/N-doped graphene interface have been synthesised using the ligand-assisted chemical vapor deposition technique.